2023
DOI: 10.1002/ijgo.14657
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the INTERGROWTH‐21st and World Health Organization fetal growth charts for the detection of small‐for‐gestational age neonates in Latin America

Abstract: Objective To evaluate the performance of INTERGROWTH‐21st (IG‐21st) and World Health Organization (WHO) fetal growth charts to identify small‐for‐gestational‐age (SGA) and fetal growth restriction (FGR) neonates, as well as their specific risks for adverse neonatal outcomes. Methods Multicenter cross‐sectional study including 67 968 live births from 10 maternity units across four Latin American countries. According to each standard, neonates were classified as SGA and FGR (birth weight <10th and less than thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
1
0
3
Order By: Relevance
“…Third, estimated fetal weight calculation was based on Hadlock-4 formula [50], which is our local practice. Finally, it has been reported that the WHO charts have a better diagnostic performance for SGA detection in Latin-American populations [52]. Longitudinal growth assessment from the second to the third trimester and delivery was performed by the calculation of z-velocity: (z-score at t 2−z-score at t 1)/interval between assessment (days) [53].…”
Section: Methodsmentioning
confidence: 99%
“…Third, estimated fetal weight calculation was based on Hadlock-4 formula [50], which is our local practice. Finally, it has been reported that the WHO charts have a better diagnostic performance for SGA detection in Latin-American populations [52]. Longitudinal growth assessment from the second to the third trimester and delivery was performed by the calculation of z-velocity: (z-score at t 2−z-score at t 1)/interval between assessment (days) [53].…”
Section: Methodsmentioning
confidence: 99%
“…den con otros estudios, como el de Fernández (18) quien, usando IG21 en una muestra de 5,442 embarazos únicos, detectó 106/5,442 (2,0%, IC 95% 1,7 a 2,4%) de recién nacidos RCIU. Es más, en un estudio con gran población latinoamericana (n= 67,968), Miranda (19) encontró una prevalencia de RCIU de 2,1% bajo los criterios de IG21 y de 6,2% según OMS, resultados muy cercanos a los nuestros (3,1% y 6,9% para IG21 y OMS, respectivamente), existiendo la duda de si el estándar de la OMS detecta más las RCIU en América Latina o si las sobrediagnostica. Lo que sí parece estar claro es el sobrediagnóstico de RCIU cuando se usa FMF, pues su tasa de detección (10,5%) es significativamente superior a los otros estándares/tablas y cuya cifra es similar a la prevalencia a nivel mundial de pequeños para la edad gestacional (PEG) caracterizados por tener < percentil 10 (20).…”
Section: Fmf: Fundación De Medicina Fetal Ig21: Proyecto Intergrowth-...unclassified
“…Estos hallazgos podrían aclarar las diferencias en las tasas de detección entre estas curvas y la interpretación de las mismas: las curvas de la OMS y FMF muestran mayor tasa de detección de RCIU que las personalizadas, pero con falsos positivos más altos. Esto explicaría, también, lo hallado en el estudio de Miranda (19) de que, aparentemente, OMS detectaba más neonatos PEG que usando IG21, pero con mayor rendimiento diagnóstico de IG21 para puntaje de Apgar e índice ponderal bajos. Debemos recordar que los falsos positivos pueden llevar a intervenciones innecesarias y ansiedad para los pacientes (20) .…”
Section: Fmf: Fundación De Medicina Fetal Ig21: Proyecto Intergrowth-...unclassified
See 1 more Smart Citation